Money laundering conviction rate and capital formation in Nigeria - Okubokeme Derek Opudu; Stanley Ogoun (Accounting, 2023)
Drawing from the Financial Action Task Force (FATF, G7) recommendations and the Nigeria Anti-Money Laundering Act that provides the penance and dissuasion for crimes in Nigeria, this study sought to interrogate the efficacy of money laundering conviction rate as an instrument of anti-money laundering policy on capital formation in Nigeria. The study is hinged on contemporary deterrence theory. The study adopted the ex-post facto research design and used quarterly data from 1Q 2010 to 4Q 2019, which was sourced from the Nigerian Financial Intelligence Unit (NFIU), Economic and Financial Crime Commission (EFCC) and CBN statistical reports. Hence, Error Correction Model (ECM) was utilized to analyze the data. The findings indicate that the current money laundering conviction rate (MLCR) has a negative and non-significant effect on capital formation in Nigeria. Therefore, the study concludes that the current conviction rate is too weak to deter the act. Hence, it is recommended that the judicial system be rejigged with enabling legislation and autonomy to strengthen it to hasten the trial of such cases and ease conviction of culpable individuals, without necessarily putting innocent victims at jeopardy. Such autonomy should also be granted to the EFCC, ICPC, NFIU etc. and inter-agency synergy should be encouraged.